2023
DOI: 10.3390/antibiotics12010182
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Selected Essential Oils against Foodborne Pathogens and Their Application in Fresh Turkey Sausages

Abstract: Essential oils (EOs) isolated from different plant materials, namely Origanum majorana L., Satureja hortensis L., and Satureja montana L. (OMEO, SHEO, and SMEO, respectively), were used in fresh turkey sausage processing. The chemical composition and in vitro antimicrobial potential of selected EOs and their mixture were determined. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against foodborne pathogens (Escherichia coli, Salmonella Enteritidis, and Listeria monocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The ripening time significantly influenced (P < 0.05) the concentration of this BA in both batches, as did starter culture inoculation, which resulted in the more intensive accumulation of tyramine in SC samples in the second half of the ripening period. This finding is in accordance with reports of several authors who previously found a highly positive correlation between the concentration of tyramine and the lactic acid bacteria counts in fermented sausages (Dominguez et al, 2016;Ikonić et al, 2023;Šojić et al, 2023).…”
Section: Effect Of the Starter Culture On Biogenic Amine Formationsupporting
confidence: 94%
“…The ripening time significantly influenced (P < 0.05) the concentration of this BA in both batches, as did starter culture inoculation, which resulted in the more intensive accumulation of tyramine in SC samples in the second half of the ripening period. This finding is in accordance with reports of several authors who previously found a highly positive correlation between the concentration of tyramine and the lactic acid bacteria counts in fermented sausages (Dominguez et al, 2016;Ikonić et al, 2023;Šojić et al, 2023).…”
Section: Effect Of the Starter Culture On Biogenic Amine Formationsupporting
confidence: 94%
“…Eur. VII procedure [ 27 ], which was described in detail in our previous work [ 2 ]. On the other hand, supercritical fluid extraction was used as a green and environmentally friendly method for isolation of lipid extracts.…”
Section: Methodsmentioning
confidence: 99%
“…In the last two decades, poultry meat production has been steadily increasing worldwide. FAO estimates that poultry meat production will reach approximately 151 million tons in 2030 [1]. Turkey meat is a source of low fat and cholesterol content, rich protein, minerals such as calcium, phosphorus, potassium, essential amino acids, and vitamins B1, B2, B6, and B12.…”
Section: Introductionmentioning
confidence: 99%